The state of infant oral healthcare knowledge and awareness: Disparity among parents and healthcare professionals - Shivaprakash P; Elango I; Baweja D; Noorani H (Wolters Kluwer Medknow Publications, 2009)
Provision of infant oral health (IOH) care is a challenging issue in the rural areas of our country due to lack of pedodontists and other dental workforces. To overcome these barriers it is essential to call the medical and other healthcare professionals to provide IOH care in joint collaboration with dental professionals. However, it is unclear to what extent these medical professionals are really aware of preventive strategies and to what extent they impart them. Thus, the present study was designed to begin from the grass-root levels, that is, assessing the baseline knowledge and awareness regarding IOH care among students (dental/medical) and parents (urban/rural). Variation of opinions with inconsistencies were obtained from both medical and/dental students and as well as from both the parental groups. This study calls for further research to evaluate the role of various factors involved in IOH care and to effectively educate all healthcare providers in this area.